627 Trauma & Orthopaedic National Selection – What Is Really Going Through the Mind of Applicants?. (12th October 2021) - Curtis, A
Abstract: Aim: Obtaining a training number in Trauma & Orthopaedics (T&O) remains highly competitive. This study aims to provide an insight into applicant's perceptions and preparation for the T&O national selection interview. Method: 162 junior doctors applying to T&O national selection in 2021 were sent questionnaires using SurveyMonkey in December 2020. Applicants were identified from those attending the annual OrthoRevision 'ST3 Core Knowledge Interview Course'. In total, 74 junior doctors (45.7%) covering all 16 surgical training regions in the UK completed feedback. Results: There were wide variations in how much applicants would spend on preparation for the interview (e.g., books, revision websites, courses): 45.9% spend £100 - £500; 21.6% spend £500-£1, 000; and 6.8% spend >£1, 000. Most start preparation 3 months prior to the interview (42.5%) with the preferred method being practice with colleagues (49.3%). Almost all candidates (80.2%) use the 'OrthoInterview' question bank. Free mock interview courses were only available to 27% with candidates strongly in favour (78%) of the study budget covering preparatory courses in addition to study leave being granted to attend these courses (86%). At the first attempt at obtaining a training number, 69.9% were selective about where they would accept a job; in subsequent years candidates would be more willing to accept a job in any deanery (40.3%). Conclusions: For the first time, we present the perceptions of applicants to T&O national training in the UK. Many candidates dedicate a large amount of time and money to the process and are initially more selective about where they apply.